Oxidation of propene and the formation of methyl nitrate in non-thermal plasma discharges - Orlandini, Igor; Riedel, Uwe (Catalysis today, 2004)
Dielectric barrier discharges are being used for plasma remediation of NOx from the exhaust of internal combustion engines, especially for diesel engines. It was found that unburned hydrocarbons (UHC) present in exhausts play a significant role in altering NO remediation pathways. For a better understanding and optimization of possible applications of this technique, it is necessary to develop models for the underlying physical and chemical processes which are responsible for the removal of pollutants. The effect of propene and propane on the removal of NO is investigated in this study including the formation of methyl nitrate. In experiments, it has been found that methyl nitrate is an important by-product of the plasma treatment of exhausts. A volume-averaged model is presented, that can describe the oxidation of hydrocarbons and conversion of NO by a multi-pulse treatment of the exhaust gases at low temperatures and at atmospheric pressure in dielectric barrier discharges. A detailed reaction mechanism is used that takes into account the production of active radicals in every discharge and the reactions induced by these radicals. Reaction flow analysis and sensitivity analysis are performed to identify specific reaction paths and rate limiting reactions for typical operating conditions of dielectric barrier discharges. A comparison of the oxidation of propene compared to propane, the analogous alkane, is presented.